Sistem Prediksi Keberhasilan Siswa Menggunakan Metode Nearest Cluster Classifier - Khairul Umam Syaliman; Edwil Jafri (Pustaka Timur Publisher, 2021)
According to present curriculum, every unit of elementary education conduct 4 (four) evaluation stages. The first stage is the first midterm evaluation which is done at the first quarter year. Second, the first semester evaluation is done at the second quarter year. Third, the second midterm evaluation is done at the third quarter year. The last is the second semester evaluation which is done at the fourth quarter year. The first midterm evaluation, the first semester evaluation and the second midterm evaluation are done to see the students’ ability in learning. Moreover, to determine the students’ success or failure in learning process at each grade is the score of the second semester which is compared to their minimum passing grade. If the students’ score is higher than the minimum passing grade decided, the students are determined to be successful. In contrary, if the students’ score is lower than minimum passing grade, they will be determined to be failed in learning process.by considering the above condition, the writer is interested in designing a system which can predict the potential failure of students earlier. This system is built by analyzing the first midterm score, the first semester score and the second midterm score by using Nearest Cluster Classifier (NCC) Method. By the result of this prediction, parents and teachers still have time for about 3 months to help and guide students who are predicted to be potentially failed in learning process.